2016
DOI: 10.21608/ajas.2016.504
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Casing Types and Cold Storage on Polycyclic Aromatic Hydro Carbons (PAHs) in Smoked Beef Sausage

Abstract: The sheep sausages casing and cellulose casings smoked in indirect traditional smokehouses were studied in order to assess the influence of smoking conditions on the PAH contents. Dependency on hot smoking conditions (with indirect smoking), using two types of casing (sheep casing and cellulose casings).All smoked samples are storage at 4C For 90 days. Smoked sausages samples by indirect technique, using smoke from an external smoke generator were assessed. The total Polycyclic aromatic hydrocarbons (PAHs) ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The levels of BaP, PAH8, and TEQ in yogurt decreased continuously, with maximum decrease rates of 56.44%, 68.32%, and 71.84% during 21 days of storage [17]. The concentration of EPA PAH16 in sheep casing and cellulose casing of smoked beef sausage reduced almost 100% from 2691 mg/kg and 599 mg/kg to 0.0026 mg/kg after 90 days of storage at 4 • C [36]. In contrast, Zhang et al [16] reported a significant increase in soybean and rapeseed oils after 270 days of storage at 4 and 25 • C. The total increase was mainly attributed to NaP due to polymerization, oxidation, and radicals.…”
Section: Variations In Pah Concentrations In Butter During Storagementioning
confidence: 98%
“…The levels of BaP, PAH8, and TEQ in yogurt decreased continuously, with maximum decrease rates of 56.44%, 68.32%, and 71.84% during 21 days of storage [17]. The concentration of EPA PAH16 in sheep casing and cellulose casing of smoked beef sausage reduced almost 100% from 2691 mg/kg and 599 mg/kg to 0.0026 mg/kg after 90 days of storage at 4 • C [36]. In contrast, Zhang et al [16] reported a significant increase in soybean and rapeseed oils after 270 days of storage at 4 and 25 • C. The total increase was mainly attributed to NaP due to polymerization, oxidation, and radicals.…”
Section: Variations In Pah Concentrations In Butter During Storagementioning
confidence: 98%
“…To this end, the characteristics of the casing surface, such as smoothness and material porosity, can contribute to inhibiting PAH penetration, implying reduced adsorption by the product [7,143,167]. For example, Youssef et al (2016) noted a 78% reduction in PAH content when replacing the original sheep intestine with a cellulose casing for smoked beef sausages [168]. Similarly, collagen is also a suitable alternative to natural animal intestinal casings in suppressing PAH contamination in sausages [108,143,169].…”
Section: Features Underlying Pah Formation In Meat and Meat-derived P...mentioning
confidence: 99%
“…Depending on the type of food, the storage period has varying effects on the PAH concentration. For example, the maximum PAH concentration in smoked sausages is detected just after smoking [168,171]. Nevertheless, during storage, PAHs may migrate inside the product and become less readily decomposable, or may interact with other substances, such as antioxidants, and undergo photochemical oxidation [171].…”
Section: Features Underlying Pah Formation In Meat and Meat-derived P...mentioning
confidence: 99%